CAPITAL ANALYSIS ON SHARIA EMPLOYEE COOPERATIVES PT. PUPUK ISKANDAR MUDA (PIM) - Sutra maulana; Radja alvarezi; Maysarah; Cut Zahrani; M.Subhan (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
As one of the business fields, cooperatives require funds to be used to run their business. In general, cooperatives are faced with the problem of increasing working capital needs to develop their business, on the other hand, the available working capital is very limited. Therefore, every cooperative is required to collect working capital from both members and non-members. In law number 25 of 1992, it is stated that sources of cooperative capital consist of own capital and loan capital. Own capital can be in the form of: principal savings, compulsory savings, reserve funds and grants. Based on Law number 25 of 1992 concerning cooperatives, in article 1 it is explained, cooperatives are business entities consisting of persons or cooperative legal entities based on their activities based on cooperative principles, as well as a people''s economic movement based on the principle of kinship. Whereas Sharia Cooperatives are business activities engaged in the field of savings and loans or services, financing and investment based on a profit sharing system (sharia).The PT Pupuk Iskandar Muda Sharia Employee Cooperative (Kopkarsyah PT PIM) was established by employees of PT Pupuk Iskandar Muda based on deed Number 1749/BH/XII/1985 dated January 11, 1985. The Articles of Association of Kopdar PT PIM have been approved by the Minister of Cooperatives and Small Entrepreneur Development of the Republic Indonesia by Decision Letter Number: 109/BH/PAD/KWK, 1/11/1997 dated March 29, 1997, then amended by the deed of Statement of Decision on Meeting Amendment to the Articles of Association Number 02 dated March 6, 2018 at Notary Nila Rufaida, SH., and has ratified by the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 000897/PAD/M.KUKM.2 /1/2019 dated January 21 2019. Based on the results of research on capital in the PT.PIM Syariah Employee Cooperative, it can be concluded that capital in KOPKARSYAH PT.PIM is obtained from members'' savings and borrowed back by these members. In managing capital, Kopkarsyah PT.PIM uses the sharia system so that the problems encountered regarding capital are very minimal. The scope of the cooperative environment is very limited, because this cooperative is only intended for employees who work within the scope of PT.PIM.